Thyroid function in hidradenitis suppurativa: a population‐based cross‐sectional study from Denmark. (21st May 2018) - Miller, I. M.; Vinding, G.; Sørensen, H. A.; Rytgaard, H.; Mogensen, U. B.; Ellervik, C.; Jemec, G. B.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disease. Numerous studies have associated HS with obesity, and recently with metabolic syndrome (MetS). Both obesity and MetS are linked with metabolic changes. Thyroid hormones play a central role in metabolism and exert pleiotropic effects on adipogenesis and the basal metabolism of lipids and glucose. We hypothesized that patients with HS have an altered or dysfunctional metabolism expressed as thyroid function. Aim: To investigate thyroid function in individuals with HS compared with healthy controls (HCs). Methods: We conducted a retrospective comparative cross‐sectional study using blood samples and questionnaire‐based self‐reported information to assess thyroid function. Results: Our study comprised 430 patients in a population‐based HS group, and 20 780 HCs. The age/sex‐adjusted analysis showed a significantly lower level ( P < 0.001) of thyroid‐stimulating hormone (TSH) and a significantly higher level ( P < 0.0001) of total triiodothyronine (tT3) for the HS compared with the HC group. The age/sex‐adjusted analysis also showed a significant association between clinical hyperthyroidism and HS (an OR = 1.91, 95% CI 1.19–3.07; P = 0.02). When this analysis was adjusted further for the potential confounders of body mass index, smoking and oral contraception, the results remained significant. Conclusion: This study suggests that HS is associated with hyperthyroidism. Hyperthyroidism may indicate an altered or dysfunctional metabolism.